Natural products as promising modulators of breast cancer immunotherapy - Alqathama, Aljawharah (Frontiers in Immunology, 2024)
Breast cancer (BC) is the most common malignancy among women and is considered a major global health challenge worldwide due to its high incidence and mortality rates. Treatment strategies for BC is wide-ranging and include surgery, radiotherapy, chemotherapy, targeted hormonal therapy and immunotherapy. Immunotherapy has gained popularity recently and is often integrated as a component of personalized cancer care because it aims to strengthen the immune system and enable it to recognize and eradicate transformed cells. It has fewer side-effects and lower toxicity than other treatment strategies, such as chemotherapy. Many natural products are being investigated for a wide range of therapeutic pharmacological properties, such as immune system modulation and activity against infection, auto-immune disease, and cancer. This review presents an overview of the major immune response-related pathways in BC, followed by detailed explanation of how natural compounds can act as immunomodulatory agents against biomolecular targets. Research has been carried out on many forms of natural products, including extracts, isolated entities, synthetic derivatives, nanoparticles, and combinations of natural compounds. Findings have shown significant regulatory effects on immune cells and immune cytokines that lead to immunogenic cancer cell death, as well as upregulation of macrophages and CD+8 T cells, and increased natural killer cell and dendritic cell activity. Natural products have also been found to inhibit some immuno-suppressive cells such as Treg and myeloid-derived suppressor cells, and to decrease immunosuppressive factors such as TGF-β and IL-10. Also, some natural compounds have been found to target and hinder immune checkpoints such as PD-L1.